The use of chitosan succinate to increase the milk production of cows - Boltianska, Natalia; Болтянська, Наталя Іванівна; Болтянская, Наталья Ивановна; Zabolotko, О. (ТДАТУ, 2020)
Et the task of studying the use of chitosan succinate with different molecular weights for black-and-white cows. Three groups of animals were selected by the method of balanced groups, taking into account age, productivity for the previous lactation, breed characteristics, live weight, etc., 15 heads each. During the study period, the animals were kept in the same conditions of feeding and keeping in accordance with zoohygienic requirements
Keywords: increasing milk; use of biologically active sub-stances; feeding of dairy cows that; chitosan